Treatment of ovarian damage induced by chemotherapeutic drugs in female rats with G-CSF and platelet-rich plasma(PRP): An immunohistochemical study correlation with novel marker INSL-3 - Çetin, Çağlar; Ökten, Sabri Berkem; Tok, Olgu Enis; Özcan, Pınar; Gökmen Karasu, Ayşe Filiz; Tanoğlu, Fatma Başak; Taha, Havva Sevde; Ateş, Seda (Taylor and Francis Ltd., 2024)
Objective: To assess the impacts of Platelet-Rich Plasma(PRP) and Granulocyte Colony-Stimulating Factor(G-CSF) on a rat model with induced ovarian follicular damage caused by cyclophosphamide(Cy).Materials and Methods: Forty-two Sprague-Dawley rats were randomly allocated into seven distinct groups as; Group 1(control): NaCl intraperitoneal (IP) injection was administered on days D1, D7, and D14. Group 2(Cy):Cy IP injection on D1 + NaCl IP injection on D7 and D14 were administered. Group 3(PRP): PRP IP injection on D1,D7 and D14 were administered. Group 4(Cy + PRP):Cy IP injection on D1 and PRP IP injection on D1, D7 and D14 were administered. Group 5(G-CSF): G-CSF IP injection on D1, D7 and D14 were administered. Group 6(Cy + G-CSF):Cy IP injection on D1+ G-CSF IP injection on D1, D7 and D14 were administered. Group 7(Cy + PRP + G-CSF):Cy IP injection on D1+ PRP IP injection on D1,D7 and D14+ G-CSF IP injection on D1,D7 and D14 were administered. Follicular number, histological scores of AMH and INSL3 stained follicles at different stages of follicular development, and serum Anti-Mullerian hormone(AMH) were evaluated.Results: The primary, secondary, and antral follicle intensity scores for AMH-positive staining were most prominent in Groups 3 and 5. There was no significant difference between groups 4, 6 and 7 compared to group 1 in terms of follicule counts and AMH staining. The intensity scores of AMH-positive staining follicles were notably reduced in group 2 compared to groups 4, 6, and 7, with a significant difference (p < .01). Among the groups, group 2 exhibited the least intense antral follicle staining for INSL3, displaying a significant difference(p < .01) compared to the remaining groups.Conclusions: Autologous PRP and G-CSF might protect ovarian function in the face of ovarian damage caused by Cy-induced effects.
Keywords: Follicle; G-csf; Ovarian Failure; InSl3 Ovary; Platelet-Rich Plasma